PENGARUH TATA KELOLA PERUSAHAAN DAN TANGGUNG JAWAB SOSIAL TERHADAP NILAI PERUSAHAAN SEKTOR PERTAMBANGAN - Aryanto Aryanto; Christina Tri Setyorini (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2019)
This study discusses corporate governance arrangements that are proxied by the board of independent commissioners, the audit board and complaints of social responsibility to the value of the company. This type of research is correlational research, with quantitative research. This study uses secondary data taken from the IDX website data. The sample used in this study proved 58 companies consisting of the mining sector during the 2-year observation period. The sampling technique was carried out using the purposive sampling method. The analytical method used is multiple linear regression analysis with an analysis tool using SPSS 22. The results of this study indicate audit audit variables have a significant effect on firm value. While the independent commissioner variables and disclosure of social responsibility are not significant to the value of the company.